Giant lithium-rich pegmatites in Archean cratons form by remelting refertilised roots of greenstone belts - Robert H. Smithies; Yongjun Lu; David C. Champion; Marcus T. Sweetapple; Jack R. Lowrey; Nathan H. Bowman; Kevin F. Cassidy; Tim J. Ivanic; Anthony I. S. Kemp; Rose E. Turnbull; Klaus Gessner; Fawna J. Korhonen (Communications Earth & Environment)
Abstract Around 80% of the world’s hard-rock lithium supply comes from pegmatites formed in the Archean Eon, yet our understanding of how Lithium-pegmatites form assumes magma source compositions not relevant to those Archean cratons hosting most of the giant Lithium-pegmatites. These models emphasize extraction of residual pegmatitic liquids from granitic magmas formed through melting sedimentary sequences. However, there is no evidence that such sequences provided the source to Lithium-rich granites and related giant Lithium-pegmatites in the Archean cratons of Western Australia. Economically important Lithium-pegmatites in these terrains form near faulted contacts between regional granites and basalt-dominated greenstone belts. Where spatially associated granites are Lithium-rich, they also contain unusually radiogenic Neodymium, resembling earlier, but spatially associated hydrated high-Magnesium diorites of mantle origin (sanukitoid). Intrusion of sanukitoids along crustal-scale structures prior to granitic magmatism induced Lithium-rich biotite alteration of the felsic basement beneath greenstone belts. Analogous to melting metasomatized lithospheric mantle to produce sanukitoids, melting of sanukitoid-infused basement beneath greenstone roots produced Lithium-rich granites and ultimately Lithium-pegmatite. Melting buried metasediments might produce Lithium-pegmatites, but most of the world’s giant Lithium-pegmatites formed along major crustal boundaries in response to the transfer of hydrous mantle-derived magma from metasomatized deep lithospheric domains in the Archean.